One-Step Formation of Chondrocytes through Direct Reprogramming via Polysaccharide-Based Gene Delivery - Qingtong Yu; Yan Wang; Xia Cao; Wenwen Deng; Michael Adu Frimpong; Jiangnan Yu; Ximing Xu (Advances in Polymer Technology)
An innovative strategy for the generation of chondrocytes was thoroughly studied in this paper. Polyetherimide-modified polysaccharides of Porphyra yezoensis (pmPPY) served as a nonviral gene vector and delivered Sox9 plasmid to directly reprogram mouse embryonic fibroblasts into chondrocytes. The gene transfer efficiency was evaluated through ELISA, RT-PCR, and Western blot. The induced chondrocytes were identified through toluidine blue, Safranin O, and the immunostaining. The expression level of collagen II was finally evaluated through western blot. The pSox9/pmPPY nanoparticles (1:50) showed lower cytotoxicity as well as greater gene transfection efficiency than Lipofectamine 2000 and polyetherimide (PEI) (p<0.05). The results of toluidine blue, Safranin O, and the immunostaining of collagen II further showed that the normal MEFs were successfully reprogrammed into chondrocytes. These findings indicate that pmPPY could be a promising gene vector for the generation of chondrocytes via single-gene delivery strategy, which might provide abundant chondrocytes for cartilage repair.